2006
DOI: 10.1152/ajpheart.01218.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiac output and microvascular blood flow during mild hemoconcentration in hamster window model

Abstract: The effect of small hematocrit (Hct) increases on cardiac index (cardiac output/body wt) and oxygen release to the microcirculation was investigated in the awake hamster window chamber model by means of exchange transfusions of homologous packed red blood cells. Increasing Hct between 8 and 13% from baseline increased cardiac index by 5-31% from baseline (P < 0.05) and significantly lowered systemic blood pressure (P < 0.05). The relationship between Hct and cardiac index is described by a second-order polynom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…In this study we characterize the changes of MAP following small changes in Hct due to isovolemic hemodilution. We compare our findings with those from previous studies with small increases in Hct (13,14) with the objective of presenting the continuum of acute cardiovascular responses due to small changes in blood viscosity within the range of variability of Hct present in the normal population. We monitored MAP and Hct after small acute isovolumic changes in Hct 2 h after the induced change in awake animals, which was a period in which the animals were hemodynamically stable.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In this study we characterize the changes of MAP following small changes in Hct due to isovolemic hemodilution. We compare our findings with those from previous studies with small increases in Hct (13,14) with the objective of presenting the continuum of acute cardiovascular responses due to small changes in blood viscosity within the range of variability of Hct present in the normal population. We monitored MAP and Hct after small acute isovolumic changes in Hct 2 h after the induced change in awake animals, which was a period in which the animals were hemodynamically stable.…”
mentioning
confidence: 72%
“…By contrast, the normal population presents a significantly smaller variability of Hct and corresponding variability of blood viscosity (11) that does not appear to influence mean arterial blood pressure (MAP) (19). However, small acute elevations of Hct (ϳ10%) in awake hamsters and mice performed by Martini et al (13,14) cause a significant lowering of MAP and elevation in cardiac output (CO) but not in endothelial nitric oxide (NO) synthase knockout mice, which do not produce NO via endothelial NO synthase. These studies and those of Salazar Vázquez et al (20) with non-oxygen-carrying, non-NO-scavenging red blood cells (RBCs) suggested that the effect due to small changes in Hct is related to the management of NO bioavailability.…”
mentioning
confidence: 99%
“…Measurements were performed at baseline and after an increase in Hct of 20% using functional RBCs. This value was chosen because this increase in Hct corresponded to levels at which MAP, CI, and VR return to baseline values (4,5). Therefore, this could be defined as a situation in which the presumed NO bioavailability increases due to augmented shear stress and is balanced by NO scavenging and the increased blood viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Martini and coworkers (4) showed that mean arterial pressure (MAP) increases only when Hct is increased 20% above baseline using functional RBCs, and that MAP decreased when the change in Hct were less than 20%. In this range, cardiac output (CO) also increased and peripheral vascular resistance (VR) decreased (4,5).…”
mentioning
confidence: 99%
“…Martine et al revealed that in a hamster model mild hemoconcentration and increased viscosity of blood augmented cardiac output and microvascular blood flow in the myocardium, and improved oxygen delivery. 21 Other potential mechanisms include optimization of preload and improved oxygen delivery to peripheral tissues, as shown by increased hematocrit, as well as reduction of systemic edema, which might favorably alter systemic vascular resistance and afterload.…”
Section: Mechanism Of Muf-induced Improvement In Ventricular Functionmentioning
confidence: 99%